THE EFFICACY OF LONG-TERM WARFARIN THERAPY: THE IMPACT ON THE INCIDENCE OF ISCHEMIC CEREBROVASCULAR DISORDERS AND CLINICAL PREDICTORS OF DEVELOPING SUCH DISORDERS. (Results of a prospective 10-year follow-up study) - E. S. KROPACHEVA; O. A. ZEMLYANSKAYA; A. B. DOBROVOLSKY; E. P. PANCHENKO («REMEDIUM GROUP» Ltd., 2017)
Atrial fibrillation (AF) is the most common indication for the long-term oral anticoagulation therapy. For several decades, vitamin K antagonists have been the mainstay of routine clinical practice.A prospective 10-year follow-up of patients with atrial fibrillation receiving warfarin therapy showed that the incidence of all cerebral circulation disorders was 2.59 per 100 patient-years. The warfarin therapy contributed to the prevailing of non-fatal events among the cerebral circulation disorders which occurred during the therapy. The incidence of fatal ischemic strokes was 0.91 per 100 patient-years over the 10-year follow-up study.If the duration of a patient within the target therapeutic range (TTR) was <70%, it increased the relative risk of ischemic cerebrovascular disorders by 2.77 times (95% CI 1.367--5.633) compared with patients with a mean value of TTR ≥ 70%.The study demonstrated that 86.5% of patients with the mean TTR values ≥ 70% had no ischemic cerebrovascular disorders for 10 years. A separate analysis of patients with high thromboembolic risk (who had 4 or more points on the CHA2DS2-VASc) showed that achieving a TTR ≥ 70% resulted in 70.7% patients who had no stroke for 10 years.The stepwise discriminant analysis revealed that the initial cognitive function decline, history of stroke and TTR <70% were predictors of developing ischemic cerebrovascular disorders (strokes and transient ischemic attacks) in patients receiving warfarin.